A Troubadours Thread - Osha, Sanya (Book collections on Project MUSE., 2013)
This volume powerfully conveys the pilgrimage of a singular spirit through adversity, equanimity, immanence and eventually, transcendence. It grapples with a range of emotions, topics and sensations. Christopher Okigbo achieved similar results but in an entirely different manner. Okigbo's vision is epical in its dimensions while Osha's work is infused with a sustained lyricism, mutedness or even more appropriately, quietude. Osha's poetry unveils a multi-layered journey from artistic infancy to complete aesthetic maturity. Most of this journey dwells upon the poet's inner states in which vast geographical vistas are revealed.